The Effectiveness of Aceh’s Special Autonomy Fund in Allocation to Poverty Alleviation, Education, and Health Sector - Fadhila, Farah; Ubaidullah, Ubaidullah; Ahmady, Iqbal (Politika: Jurnal Ilmu Politik, 2023)
This research aims to analysis the effectiveness of the allocation of Aceh’s special autonomy fund for development in the sectors of poverty alleviation, education, and health during the period of 2017 to 2022. The method used in this study is qualitative descriptive with the data collection techniques are interviews and documentation. Moreover, this research focus on the existence of Aceh as an asymmetric decentralization. The theory that used to strengthen the argument is public management theory and used the concept of effectiveness. The result showed that during the period of Irwandi Yusuf-Nova Iriansyah, the allocation of Aceh’s special autonomy fund has not been effective for development in Aceh, especially in the sector of poverty, improving the quality of education and health. It is because of the management of the special autonomy fund’s allocation is not optimal implemented since the planning to the controlling. It has the impact to the allocation of Aceh’s special autonomy fund which is not well-targeted to achieve the goals and to improve the society’s welfare.